Effect of aqueous and alcoholic extracts of Mushroom Calvatia craniiformis in bone marrow and interferon Gamma in mice (Baghdad Science Journal, 2013)
This research was designed to study the effect of water and alcoholic crude extracts of Calvatia craniiformis in vitro and in vivo On the other hand this study tested the toxic effect of both extracts in normal laboratory mice. The results showed that water and alcoholic extracts relatively have an acute toxic effect in mice in respect to LD50 (85 mg/kg, and 177mg/kg respectively). However the chronic toxicity of water extract at three different concentration (50, 75, 100 mg/kg) and alcoholic extract at concentrations of (100, 150, 200 mg/kg) was investigated in normal mice by (I.P) administration for 30 days alternatively and one drag in 48 hours . The results indicated significant effect (P ? 0.01) increasing in (MI) and (BI) of bone marrow cells and serum IFN-? level. Also both extract caused inhibitory effect in each of (MI) and (BI), however they should significant increase (P ? 0.01) in the serum level of IFN-? but no significant in Phagocytosis and control.